DESAIN TEBAL PERKERASAN TERHADAP VOLUME LALU LINTAS PADA KONDISI TANAH RAWA JALAN LABUHA–TOMORI BACAN KABUPATEN HALMAHERA SELATAN - Chairul Anwar; M Taufik Yudha Saputra (Fakultas Teknik Universitas Khairun, 2018)
This research was carried out on Jalan Oesman Shah on Labuha-Tomori Road. In determiningflexible pavement thickness, based on the results of analysis and calculation of PavementThickness Design Against Traffic Volume on Swamp Conditions on the Labuha-Tomori RoadSection using the Road Pavement Design Manual Number 02 / M / BM / 2013. Based on theexisting plan, this Labuha-Tomori road section in South Halmahera Regency, North MalukuProvince is an arterial road with 2-lane 2-way road type using the median (2/2 UD), plan width of10 meters, width of existing traffic lane 4, 5 meters, median width of 1 meter, and plannedshoulder width 2.40 m. Based on the results of the analysis of growth rates obtained traffic growthrates of 33.066% over the life of the plan, determining the distribution factor of the lane and thecapacity of the lane of lane 1 and the vehicle in the design lane taken 100%. The equivalent loadfactor can be determined using the value of VDF (Vehicle Damage Factor) according to thesurvey results in the field. The traffic volume plan to determine the CESA4 value = 18,835,021.85= 18.84 million is used for the selection of pavement types while the CESA5 value =33,903,039.33 = 33.90 million is used to determine the type of flexible pavement based on thedesign chart provided in The Road Pavement Design Manual Number 02 / M / BM / 2013, ishighly emphasized in terms of the improvement of subgrade, by looking at the condition of theCBR of the subgrade and CESA5 which will be received by pavement. So if the pavement CBR is5.20% and CESA5 is 33.90 Million, the flexible pavement design is of 2 kinds in the design ofpavement thickness: AC - WC = 4 cm, AC - BC = 15.5 cm, CTB = 15 cm, LPA Class A = 15 cm,Choice of 10 cm and AC - WC = 4 cm, AC - BC = 6 cm, AC BASE = 18 cm, LPA = 30 cm, Choiceof Stock = 10 cm, and Subgrade = 5.20%